2006
DOI: 10.1016/j.yrtph.2006.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Food-processing enzymes from recombinant microorganisms—a review

Abstract: Enzymes are commonly used in food processing and in the production of food ingredients. Enzymes traditionally isolated from culturable microorganisms, plants, and mammalian tissues are often not well-adapted to the conditions used in modern food production methods. The use of recombinant DNA technology has made it possible to manufacture novel enzymes suitable for specific food-processing conditions. Such enzymes may be discovered by screening microorganisms sampled from diverse environments or developed by mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
137
0
7

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 289 publications
(145 citation statements)
references
References 75 publications
(77 reference statements)
0
137
0
7
Order By: Relevance
“…Fungi selected for initial evaluation included Aurobasidium pullulans, Trichoderma reesei, Fusarium venenatum, Pichia kudriavzevii, and Mucor circinelloides. Several of these fungi are known to produce cellulose degrading enzymes (Wiebe, 2002;Olempska-Beer, Merker, Ditto, & DiNovi, 2006;Seiboth, Ivanova, & Seidl-Seiboth, 2011;Prajapati, Jani, & Khanda, 2013;Ratledge, 2013). Studies have shown that F. venenatum is capable of producing mycotoxins, however their production can be avoided by controlling fermentation conditions (Wiebe, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Fungi selected for initial evaluation included Aurobasidium pullulans, Trichoderma reesei, Fusarium venenatum, Pichia kudriavzevii, and Mucor circinelloides. Several of these fungi are known to produce cellulose degrading enzymes (Wiebe, 2002;Olempska-Beer, Merker, Ditto, & DiNovi, 2006;Seiboth, Ivanova, & Seidl-Seiboth, 2011;Prajapati, Jani, & Khanda, 2013;Ratledge, 2013). Studies have shown that F. venenatum is capable of producing mycotoxins, however their production can be avoided by controlling fermentation conditions (Wiebe, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…They are water-soluble enzymes that act in catalyzing the hydrolysis of ester bonds in water-insoluble lipid substrates (Guo and Xu 2005). Lipases are ubiquitously produced by the plants (Bhardwaj et al 2001;Belguith et al 2009); animals (Carriere et al 1994); and microorganisms (Olempska-Beer et al 2006;Ramesh et al 2013). Microbial lipases are the preferred potent source due to several industrial potentials (Hasan et al 2006;Riaz et al 2010;Veerapagu et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The deletion of native genes encoding extracellular proteases, for example, increased enzyme production yields of microbial hosts. In fungi, for example, the production of toxic secondary metabolites has been reduced to improve their productivity as enzyme-producing hosts (Olempska-Beer et al, 2006).…”
Section: Application Name Example Reference(s)mentioning
confidence: 99%